Perempuan Single Parent Bekerja Sebagai Driver Ojek Online di Pekanbaru - Agung Dermawan Sembiring; Achmad Hidir (Pusat Riset dan Inovasi Nasional, 2023)
Single parent women have multiple activities and responsibilities towards their families. So that in fulfilling their needs of family life, single parent women must be able to balance their domestic and public affairs, especially when they are working. The job they are chosen is a job with high time flexibility, one of which is by becoming an online motorcycle driver. they meet various people every day, friends from a basecamp, from customers and parties they meet and their activities in order to get sustenance for the needs of their family life. The purpose of this study was to find out the rational choice of single parent women to become online motorcycle drivers in Pekanbaru City. The research method used is descriptive qualitative with purposive sampling technique. Data collection techniques used are observation, interviews and documentation. Data analysis uses rational choice theory by james coleman. The results of this study indicate that single parent women working as online motorcycle drivers have their own way of dividing time for domestic and public activities, and have many friends